Multifunctional role of GPCR signaling in epithelial tube formation. - Vishwakarma, V.; Le, T.P.; Chung, S. (Development, 2022)
Epithelial tube formation requires Rho1-dependent actomyosin contractility to generate the cellular forces that drive cell shape changes and rearrangement. Rho1 signaling is activated by G-protein-coupled receptor (GPCR) signaling at the cell surface. During Drosophila embryonic salivary gland (SG) invagination, the GPCR ligand Folded gastrulation (Fog) activates Rho1 signaling to drive apical constriction. The SG receptor that transduces the Fog signal into Rho1-dependent myosin activation has not been identified. Here, we reveal that the Smog GPCR transduces Fog signal to regulate Rho kinase accumulation and myosin activation in the medioapical region of cells to control apical constriction during SG invagination. We also report on unexpected Fog-independent roles for Smog in maintaining epithelial integrity and organizing cortical actin. Our data support a model wherein Smog regulates distinct myosin pools and actin cytoskeleton in a ligand-dependent manner during epithelial tube formation.